Study on the test of coal mass fracture grouting sealing with coal-based materials and its application - Gao, Yingjun; Yao, Banghua; Zhang, Hongtu; Zhang, Boyang; Song, Jinhu; Wang, Qian; Niu, Jinming; Li, Jinhua (Frontiers in Earth Science, 2023)
This study is focused on coal mass fracture grouting sealing and seepage reduction with coal-based grouting sealing materials. First, a new type of coal-based grouting sealing materials was developed and applied to the fractured coal sample in the grouting test. Then, the coal sample before and after grouting was scanned and reconstructed with the aid of industrial computed tomography (CT). Based on CT images and reconstructed data, a theoretical model of grouting sealing for fractured coal mass was constructed by taking the migration and sedimentation of grouting slurry particles into consideration. Furthermore, on the ground of the theoretical model, a numerical calculation model of grouting sealing for the fractured coal sample was established, and the mechanism of grouting sealing and seepage reduction with coal-based sealing materials was simulated. Finally, a field test of gas extraction drilling and sealing was performed using the coal-based grouting sealing technology. The results show that: 1) The new type of coal-based grouting materials is effective in sealing the coal mass fracture, as the fracture is tightly filled with slurry particles after grouting. 2) The numerical simulation reproduces the whole process of grouting slurry flow and fracture sealing. After the permeability of the grouting coal sample decreases rapidly, it gradually tends to stabilize. The permeability of the whole coal sample goes down by 96% on average, and that of the fracture drops by more than 99.9% on average. The law of slurry diffusion and permeability variation calculated by numerical simulation is in line with the test results, which verifies the reasonableness of the model. 3) The application of the coal-based grouting sealing technology achieves an excellent sealing effect, promoting the gas extraction concentration by 1.43 times. The research results provide guidance for revealing mechanism of coal mass fracture grouting sealing with coal-based materials and bolstering the effect of extraction borehole sealing.